The feasibility of Picture-Based Insurance (PBI): Smartphone pictures for affordable crop insurance - Ceballos, Francisco; Kramer, Berber; Robles, Miguel (Elsevier, 2019)
Smallholder farmers are increasingly exposed to weather extremes but lack access to affordable insurance products for catastrophic crop damage. This paper analyzes the feasibility of Picture-Based Insurance (PBI) as a low-cost tool to improve coverage. PBI verifies insurance claims using smartphone pictures of insured plots, taken by farmers themselves, to minimize asymmetric information and costs of claims verification, while reducing basis risk compared to index-based insurance. A pilot implementation in the rice-wheat belt of India speaks to PBI being a feasible and valuable innovation to reduce downside basis risk in index insurance: nearly two-thirds of trained farmers took at least four pictures (roughly one per growth stage), which was considered sufficient for loss assessment; severe damage was visible from smartphone pictures in 71 percent of affected sites; and this was a significant improvement over alternative index-based products, which identified severe damage in at most 34 percent of affected sites.